Power Consumption Modeling and Analysis of Integrated Optical-Wireless Access Network - A. Ramli; N. Zulkifli; S. M. Idrus (Institute of Advanced Engineering and Science, 2017)
The integration of optical and wireless technologies at access networks are considered as a future solution which provide both high bandwidth and high mobility in an efficient way. GPON is a suitable candidate for optical backhaul due to the combination of higher data rates, greater split ratio and support for triple play services hence it offers maximum flexibility and cost advantages. On the other hand, recent developments of new radio access technologies and introduction of femtocell base stations provide the potential of offering broadband services and applications to everyone and everywhere. However, the power consumption of this network demands a particular attention because access networks are the largest contributor the network related electricity consumption. Therefore, in this paper we evaluate the power consumption of integrated optical-wireless access network which is based on independent ONU-BS architecture. We proposed a power consumption model for such network and the assessment has been done under different simulation scenarios. The constructed model will provide insight of the energy performance of the integrated access network so that in the network design process, focus can be done to the most energy saving strategies.